2014
DOI: 10.1371/journal.pone.0094171
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of FLOWERING LOCUS T1 (FT1) Gene in Brachypodium and Wheat

Abstract: The phase transition from vegetative to reproductive growth is a critical event in the life cycle of flowering plants. FLOWERING LOCUS T (FT) plays a central role in the regulation of this transition by integrating signals from multiple flowering pathways in the leaves and transmitting them to the shoot apical meristem. In this study, we characterized FT homologs in the temperate grasses Brachypodium distachyon and polyploid wheat using transgenic and mutant approaches. Downregulation of FT1 by RNAi was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 52 publications
12
120
0
Order By: Relevance
“…The delay in heading time observed in the tetraploid phyC AB mutant under LD is more than threefold longer than that observed in the triple ppd1-null mutant in hexaploid wheat (42) and that reported for the FT1 mutants in tetraploid Kronos (43). This result suggests that additional genes regulated by PHYC contribute to early flowering of wheat under LD.…”
Section: Phyc Is Involved In the Transcriptional Regulation Of Bothmentioning
confidence: 54%
See 1 more Smart Citation
“…The delay in heading time observed in the tetraploid phyC AB mutant under LD is more than threefold longer than that observed in the triple ppd1-null mutant in hexaploid wheat (42) and that reported for the FT1 mutants in tetraploid Kronos (43). This result suggests that additional genes regulated by PHYC contribute to early flowering of wheat under LD.…”
Section: Phyc Is Involved In the Transcriptional Regulation Of Bothmentioning
confidence: 54%
“…Under LD, PPD1/PRR37 up-regulates FT1 in barley and wheat (25) but down-regulates FT homologs in rice and sorghum (58,59). Upregulation of FT1 in wheat is associated with the up-regulation of FT2 (43,71), which also promotes flowering (72). (Pathway B) PHYC also modulates the expression of circadian clock and clock output genes CO1 and CO2.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are several FT homologs in Brachypodium, a recent study indicates that one of them, which is phylogenetically most closely related to Arabidopsis FT, is the primary promoter of flowering, as knockdown of its expression results in a severe delay of flowering (Lv et al 2014). We have shown that this FT homolog is not expressed in phyC mutants and that overexpression of this FT is able to rescue the delayed flowering phenotype of phyC.…”
Section: Phyc Plays a Major Role In Photoperiodic Flowering In Pooidsmentioning
confidence: 72%
“…FT enhances VRN1 expression, "locking in" VRN2 repression and the promotion of flowering (Yan et al 2006;Shimada et al 2009). The proposed feedback model resulting from studies in wheat and barley appears to be largely conserved in Brachypodium (Lv et al 2014;Ream et al 2014) except that the role of VRN2L is less clear as it is up-regulated in the cold .…”
Section: Phyc Plays a Major Role In Photoperiodic Flowering In Pooidsmentioning
confidence: 99%
“…The insertion of a repetitive element in the regulatory region of Vrn-B3 in wheat variety Chinese Hope produces a dominant allele and early flowering. Transgenic winter wheat overexpressing the Vrn-B3 allele flowers earlier than the control without vernalization treatment (Yan et al 2006), suggesting that the dominant VRN3 allele can overcome the repression of VRN2 and bypass the vernalization requirement, while downregulation of FT1 expression by RNA interference results in late flowering in wheat (Lv et al 2014).…”
Section: Introductionmentioning
confidence: 99%